LEGAL CONDITIONS FOR THE CONSTITUTIONAL COMPETENCES OF STATE AUTHORITIES IN A SECURITY AND DEFENSE SPHERE IN THE CONTEXT OF INTERNATIONAL POLICY (Research Bulletins of the Faculty of Economic Sciences, 2019)
The purpose of this article is to systematize legal, national and international regulations in the areas of security and defense policy of the Republic of Poland and making the reader aware of the legal and legal status of the state, which currently creates all conditions for a comprehensive ordering of security and defense matters in Poland. The article justifies the need for political will of state authorities and persons responsible for continuity of creating conditions for security and defense in the context of sustainable development of the state.
Keywords: defense policy, international policy, state organs, formal and legal conditions, sustainable development